2013
DOI: 10.1111/iju.12049
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors predicting the outcome of salvage radiotherapy in patients with biochemical recurrence after radical prostatectomy

Abstract: Abbreviations & Acronyms ADT = androgen deprivation therapy CI = confidence interval c-index = concordance index CT = computed tomography DT = doubling time GS = Gleason score HR = hazard ratio pGS = Gleason score of prostatectomy PSA = prostate-specific antigen PSA-DT = prostate-specific antigen doubling time RT = radiotherapy Objectives: Salvage radiotherapy is the only curative treatment for patients with prostate cancer showing biochemical progression after radical prostatectomy. In this study, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Stephenson et al reported that patients with positive surgical margins are more likely to have better prognoses after salvage RT than those with negative margins (HR 1.7, 95% CI 1.4–2.5, p<0.001) [24]. Also Kinoshita et al reported that a negative surgical margin was an independent predictor of BCR-free survival after salvage RT (HR 0.28, 95% CI 0.12–0.70, p = 0.006) [25]. The overall analysis of the patients in the present study suggested that a positive surgical margin was a statistically significant predictor of longer BCR-free survival after salvage RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stephenson et al reported that patients with positive surgical margins are more likely to have better prognoses after salvage RT than those with negative margins (HR 1.7, 95% CI 1.4–2.5, p<0.001) [24]. Also Kinoshita et al reported that a negative surgical margin was an independent predictor of BCR-free survival after salvage RT (HR 0.28, 95% CI 0.12–0.70, p = 0.006) [25]. The overall analysis of the patients in the present study suggested that a positive surgical margin was a statistically significant predictor of longer BCR-free survival after salvage RT.…”
Section: Discussionmentioning
confidence: 99%
“…BCR after RP was defined as a PSA level of ≥0.2 ng/mL with 2 consecutive increases from a PSA value of <0.2 ng/mL, a PSA level that did not reduce to <0.2 ng/mL and increased twice, or the initiation of salvage therapy [4], [5]. The date on which BCR occurred was defined as the day on which the PSA level increased to ≥0.2 ng/mL or the day of the first follow-up visit if the PSA value did not decrease under 0.2 ng/mL [4].…”
Section: Methodsmentioning
confidence: 99%
“…In this meta-analysis, eight studies evaluated the surgical margins910131416171920 However, the overall effect showed no significant association between surgical margins and BCR (OR: 1.09; 95% CI: 0.83–1.43). The fixed-effects model was reported here because there was no evidence of heterogeneity ( I 2 = 30%) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 86%
“…BCR after RP was defined as PSA level ≥0.2 ng ml −1 with two consecutive increases from a baseline of <0.2 ng ml −1 . BCR after SRT was defined as a PSA level that had increased to ≥0.2 ng ml −1 from the post-RT nadir confirmed by one more consecutive result 1718…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation